PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN SELEKSI PENERIMA BANTUAN PKH (PROGRAM KELUARGA HARAPAN) MENGGUNAKAN METODE SAW (STUDI KASUS : DINAS SOSIAL KABUPATEN CIREBON) - Khairul Anwarudin; Imanda; Yumna Nabila (Program Studi Teknik Informatika Universitas Muhammadiyah Cirebon, 2026)
This study examines the development of a Decision Support System (DSS) to assist the selection process of beneficiaries of the Program Keluarga Harapan (PKH) at the Social Service Office of Cirebon Regency, considering that the current selection process is still conducted manually, which may lead to inaccurate targeting, lack of transparency, and low efficiency, potentially resulting in unfair distribution of social assistance; therefore, a computerized system is required to support decision making in a more systematic manner by considering criteria established by the government. The purpose of this study is to design and implement a DSS based on the Simple Additive Weighting (SAW) method, which is capable of performing weighting and ranking of beneficiary alternatives according to criteria such as pregnant women, school-age children, the elderly, persons with disabilities, and household income, so that the resulting decisions are more objective, fair, and well-targeted. The system is developed using the Laravel framework and a MySQL database, and follows the Waterfall software development model, while data are collected through observation, interviews, and literature review. The implementation results indicate that the system is able to perform normalization, weighting, and ranking processes to determine eligible PKH beneficiaries in accordance with the defined criteria, thereby supporting the Social Service Office of Cirebon Regency in distributing assistance more efficiently, transparently, and accurately.